2011
DOI: 10.1016/j.jsv.2011.03.027
|View full text |Cite
|
Sign up to set email alerts
|

H-infinity optimization of a variant design of the dynamic vibration absorber—Revisited and new results

Abstract: The H ∞ optimum parameters of a dynamic vibration absorber (DVA) with ground-support are derived to minimize the resonant vibration amplitude of a single degree-of-freedom (SDOF) system under harmonic force excitation. The optimum parameters which are derived based on the classical fixed-points theory and reported in literature for this non-traditional DVA are shown to be not leading to the minimum resonant vibration amplitude of the controlled mass. A new procedure is proposed for the H ∞ optimization of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…[7,8] and references therein), the above discussed "classical" TMD configuration (mass attached via a spring and a dashpot in parallel) is the most widely studied in the literature and the most commonly used one for passive vibration control of various mechanical and civil engineering structures and structural components. In particular, motivated mostly by earthquake engineering applications, substantial research work has been devoted to investigate the potential of using the classical TMD to mitigate the motion of stochastically support-excited primary structures.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] and references therein), the above discussed "classical" TMD configuration (mass attached via a spring and a dashpot in parallel) is the most widely studied in the literature and the most commonly used one for passive vibration control of various mechanical and civil engineering structures and structural components. In particular, motivated mostly by earthquake engineering applications, substantial research work has been devoted to investigate the potential of using the classical TMD to mitigate the motion of stochastically support-excited primary structures.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, substituting all the parameters into Eq. (11) and searching numerically for the damping coefficient which gives the minimum area of the transmissibility yields z¼0.1510. The obtained parameters of the 2dof TVA are listed in Table 1.…”
Section: Numerical Examplementioning
confidence: 99%
“…For example, Snowdon [9] considered a three-element TVA in which the damper is connected in series with a spring and showed that such a device can be more effective than a conventional TVA of the same mass. More recently Cheung and Wong [10][11][12] studied a TVA where the damper is connected to the ground instead of the mass of the host structure. Other researchers have tried also to introduce nonlinearities in the TVA to improve the performance, for example [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, how to optimize the parameters of TMDs (e.g., the natural frequency, the mass, and the damping ratio) to achieve a best vibration effect subjected to constrained budget is a key challenge. Single degree‐of‐freedom (SDOF) systems have been used by many researchers (e.g., Sadek et al, Krenk and Høgsberg, Cheung and Wong, Xiang and Nishitani) to study the parameter optimization of TMDs. However, single degree‐of‐freedom systems are clearly unsuitable for super‐tall buildings.…”
Section: Introductionmentioning
confidence: 99%